Adiposity distribution influences circulating adiponectin levels - Guenther, Mitchell (Transl Res, 2014)
Thirty percent of obese individuals are metabolically healthy and were noted have increased peripheral obesity. Adipose tissue is the primary source of adiponectin, an adipokine with insulin-sensitizing and anti-inflammatory properties. Lower adiponectin levels are observed in individuals with obesity and those at risk for cardiovascular disease. Conversely, higher levels are noted in some obese individuals who are metabolically healthy. Our objective was to determine whether abdominal adiposity distribution, rather than BMI status, influences plasma adiponectin level. Four-hundred and twenty-four subjects (female: 255) of Northern European ancestry were recruited from “Take Off Pounds Sensibly” (TOPS) weight loss club members. Demographics, anthropometrics, and dual X-ray absorptiometry of the whole body and CT scan of the abdomen were performed to obtain total body fat content and to quantify subcutaneous adipose tissue and visceral adipose tissue respectively. Laboratory measurements included fasting plasma glucose, insulin, lipid panel, and adiponectin. Age- and gender-adjusted correlation analyses showed that adiponectin levels were negatively correlated with body mass index, waist circumference, triglycerides, total fat mass, and visceral adipose tissue. A positive correlation was noted with HDL-cholesterol and fat free mass (p<0.05). Subcutaneous adipose tissue -to-visceral adipose tissue ratios were also significantly associated with adiponectin (r=0.13, p = 0.001). Further, the best positive predictors for plasma adiponectin were found to be subcutaneous adipose tissue -to-visceral adipose tissue ratios and gender by regression analyses (P<0.01). Abdominal adiposity distribution is an important predictor of plasma adiponectin and obese individuals with higher subcutaneous adipose tissue -to-visceral adipose tissue ratios may have higher adiponectin levels.